2018
DOI: 10.1186/s12889-018-6000-x
|View full text |Cite
|
Sign up to set email alerts
|

Casual alcohol consumption is associated with less subclinical cardiovascular organ damage in Koreans: a cross-sectional study

Abstract: BackgroundEpidemiologic studies have presented protective effects of alcohol against cardiovascular (CV) events. However, such studies were performed mainly on Westerners. We investigated the effects of alcohol on the subclinical CV morbidity in healthy Koreans.MethodsThe coronary artery calcium (CAC) score, ankle-brachial pulse wave velocity (abPWV), and carotid intima-media thickness (cIMT) of 1004 subjects (age, years±standard deviation [SD] 53 ± 10; 72% were men) with no CV disease history were assessed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…1 a, b Dose-response relationships between alcohol consumption and each of the considered measurements of C-IMT (p50) at baseline (a) and progression (b). Solid lines: Restricted cubic splines adjusted for sex, age, physical activity, smoking, diet, and latitude, with knots located at fixed points of g/d of alcohol consumption (4,10,20,30). Dashed lines: 95% CI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 a, b Dose-response relationships between alcohol consumption and each of the considered measurements of C-IMT (p50) at baseline (a) and progression (b). Solid lines: Restricted cubic splines adjusted for sex, age, physical activity, smoking, diet, and latitude, with knots located at fixed points of g/d of alcohol consumption (4,10,20,30). Dashed lines: 95% CI.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from epidemiological studies investigating the association between alcohol consumption and C-IMT have shown inconsistent results: some found a protective effect of moderate alcohol consumptions [9][10][11][12][13][14][15][16][17][18][19][20], others suggested that alcohol is always a risk factor [21][22][23][24][25][26], and yet others showed no association [27][28][29][30][31][32][33][34][35]. Some of the studies have described the relationship between alcohol consumption and atherosclerosis as linear, with either increased [22,25] or decreased C-IMT [13,16] associated with a rise in alcohol consumption, whereas others report a J-shaped association, with a decrease of C-IMT with moderate alcohol consumption and an increase of C-IMT with high alcohol consumption [9,14,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Among environmental factors, dietary compounds were explored only to a limited extent, and most previous studies have been focused on exploring the role of salt consumption on PWV increase [ 11 , 12 ]. Nevertheless, beverages represent a consistent part of daily diet; alcohol is one of the most consumed—as well as abused—beverages worldwide, and it is in turn considered as a factor influencing arterial stiffness [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 Regarding alcohol consumption, patients were considered ‘problem drinkers’ if they consumed more than 14 standard drinks a week. 6 Economic status was assessed by family size-adjusted mean monthly household income calculated by dividing household income by the square root of the number of persons in the household. We defined the lowest quartile as ‘low income level’.…”
mentioning
confidence: 99%